A poem for every day of the year - Esiri, Allie 1967- (Macmillan Children's Books, 2017)
ANTHOLOGIES (CHILDREN'S / TEENAGE). A Poem For Every Day of the Year is a magnificent collection of 366 poems compiled by Allie Esiri, one to share on every day of the year. These poems are funny, thoughtful, inspiring, humbling, informative, quiet, loud, small, epic, peaceful, energetic, upbeat, motivating, and empowering! Perfect for reading aloud and sharing with all the family, it is bursting at the seams with familiar favourites and exciting new discoveries. T.S.Eliot, John Betjeman, Lewis Carroll, William Shakespeare and Christina Rossetti sit alongside Seamus Heaney, Ted Hughes, Carol Ann Duffy, and Kate Tempest. Age 9+